Delivery of a western-centric initial teacher education award in a Chinese-centric context. What constitutes good practice?. Issue 2 (14th March 2020) - Machin, Lynn; Richardson, Tina; Ryan, Matt
ABSTRACT: This paper has two purposes. First, to explore ways in which a western-centric in-service teacher education programme has transformed the teaching of 14 teacher participants who hitherto used a more Chinese-centric approach to teaching. Second, to investigate if any changes that have occurred have diffused beyond the teacher participants' classrooms and if so, to whom and to where. The teacher participants belonged to one of four cohorts of teachers who, between 2014–2019, enrolled onto a UK accredited, level seven, Post Graduate Certificate (International) Education (PGCIE), blended learning programme. All used English as the medium of instruction to teach English, Accounts or Business subjects to Chinese students, aged 18–23. Underpinned by principles of pedagogical gains through reflective practice, the programme's aim was to develop teacher participants' practice, with an emphasis on student-led approaches to teaching and learning. Tenets of two theoretical frameworks (transformational learning and diffusion of innovations) furnished a lens to view the data. Data were gathered from interviews with teacher participants and managers. Available and relevant statistical data were also used. The paper presents evidence of how transformational learning leads to improved teacher effectiveness and how changes in practice can become diffused beyond the classroom and to others.